Tinjauan Yuridis terhadap Proses Pemberian Ganti Kerugian Pengadaan Tanah bagi Pembangunan untuk Kepentingan Umum dalam Pembangunan Pelabuhan Terminal Multipurpose Kualatanjung di Kabupaten Batubara - Silalahi, Rizki Natalina; Isniani, Isniani; Limbong, Dayat (Mahesa Research Center, 2022)
The aim of the study was to analyze the application of Law Number 2 of 2012 in the public interest to the process of granting compensation for land in land acquisition for development in the public interest in the construction of the Kualatanjung Multipurpose Terminal Port in Batubara Regency and the constraints encountered. The research method used is normative legal research, with data collection instruments namely interviews and documentation as well as data analysis using descriptive analysis. Based on research, the application of Law Number 2 of 2012 to the process of granting compensation for land in land acquisition in the construction of the Kualatanjung Multipurpose Terminal Port in the Regency is carried out through: a. Planning, b. Preparation, c. implementation, d. submission of results. The obstacles encountered during the compensation process for the land acquisition process for the construction of the Kualatanjung Multipurpose Terminal Port in Batubara Regency, namely: a. Lack of awareness and understanding of the community about the meaning of development for the public interest, b. rejection of the amount of compensation, c. there are people who do not have land rights, d. many people did not attend the process of measuring land plots, e. there are disputes over land objects controlled by landowners with other parties that have not been resolved.